2021
DOI: 10.3390/molecules27010101
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Delocalization in an Asymmetric Biomolecule: The Curious Case of Alpha-Fenchol

Abstract: Rotational microwave jet spectroscopy studies of the monoterpenol α-fenchol have so far failed to identify its second most stable torsional conformer, despite computational predictions that it is only very slightly higher in energy than the global minimum. Vibrational FTIR and Raman jet spectroscopy investigations reveal unusually complex OH and OD stretching spectra compared to other alcohols. Via modeling of the torsional states, observed spectral splittings are explained by delocalization of the hydroxy hyd… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 124 publications
(245 reference statements)
1
7
0
Order By: Relevance
“…10,25 Subsequent investigation employing FTIR and Raman jet spectroscopy and helium as carrier gas revealed the second and third conformer. 53 However, it was concluded that the hydroxy hydrogen atom is highly delocalized between positions A and B through a tunnelling interaction facilitated by an energetic near-degeneracy as well as a low and narrow interconversion barrier. The difference between the two lowest torsional states was determined as 0.19(1) kJ mol −1 , which represents an upper bound for the difference between the calculated hypothetical localized conformers A and B due to the also contributing tunnelling splitting.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…10,25 Subsequent investigation employing FTIR and Raman jet spectroscopy and helium as carrier gas revealed the second and third conformer. 53 However, it was concluded that the hydroxy hydrogen atom is highly delocalized between positions A and B through a tunnelling interaction facilitated by an energetic near-degeneracy as well as a low and narrow interconversion barrier. The difference between the two lowest torsional states was determined as 0.19(1) kJ mol −1 , which represents an upper bound for the difference between the calculated hypothetical localized conformers A and B due to the also contributing tunnelling splitting.…”
Section: Resultsmentioning
confidence: 99%
“…This means this level of theory somewhat overestimates the E (B)– E (A) difference, as other tested DFT methods do. 53 In the complex with camphor, the tunnelling is expected to be quenched.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5.4, labelled "1D(ICP)". They were obtained with a recent computer implementation of the Chung-Phillips ansatz [257] that was published by Medel et al [258]. Note that there are deviations 178 to recently published values by Hull et al [107].…”
Section: The Oh Torsionmentioning
confidence: 98%